Cultural Determination of Cause-Effect. On a Possible Folk Model of Causation - Bernárdez, Enrique (Círculo de Lingüística Aplicada a la Comunicación, 2023)
Even though the basic causative constructions in Spanish correspond to the FORCED MOVEMENT metaphor, the folk model of CAUSE that underlies them sees the world on terms of the naturalness of things and courses of events, not so much on the terms of CAUSATION proper. In the Navajo and Samoan constructions, the forced movement metaphor does not seem to play a significant role. At the same time, both languages-and-cultures differ in the general way of conceptualising and expressing CAUSE, and their respective conceptualisations seem to be fairly coherent with other basic features of their cultures. We can thus assume that both the conceptualisation(s) and linguistic expressions of cause and causation will be heavily dependent on, and determined by, the different cultures.